The site of Ayios Vasileios in Laconia from the prehistoric to the early modern period. Results of the pedestrian field survey - Wiersma, Corien; Bes, Philip; van IJzendoorn, Mink W.; Wiznura, Adam; Voutsaki, Sofia (Journal of Greek Archaeology, 2022)
The Ayios Vasileios Survey Project is part of the Ayios Vasileios Excavations Project. The broader project includes the excavations of the Mycenaean palace and the early Mycenaean North Cemetery. The survey project consists of a pedestrian survey and a geophysical exploration of the area, and is accompanied by an ethnographic survey. In this article we discuss the results of the pedestrian survey and offer a reconstruction of the habitation history of the site. In the following discussion, we first introduce the site of Ayios Vasileios and sketch a brief outline of the research carried out at the site thus far and its habitation history. Secondly, we present the pedestrian survey methodology. This is followed by an extensive discussion of the distribution and date of the collected surface material for the main periods attested at the site: the Bronze Age, the Classical-Hellenistic, the Roman, and the Medieval and Early Modern. The spatial and temporal patterns are contextualised and compared with data generated by the excavation and geophysical research already published. The integration of these different data allows us to provide a more detailed reconstruction of the extent and spatial development of the site through time.